Complete resolution of juvenile neuropsychiatric lupus with low dose rituximab (Indian Journal of Case Reports, 2021)
Nervous system involvement leads to high mortality in juvenile systemic lupus erythematosus. We present the case of a 12-year-old girl who was admitted with a history of recurrence of fever, cervical swellings, seizure, and delirium. Approximately 6 months back, she was started on antitubercular therapy (ATT) for fever and granulomatous lymphadenitis. She developed a recurrence of fever, new cervical swellings, seizures, and delirium while she was continuing ATT. Magnetic Resonance Imaging brain revealed multiple hyperintensities in bilateral basal ganglia, temporal, and hippocampal regions. The patient was diagnosed to have lupus based on clinical features, positive antinuclear antibody, positive double-stranded DNA antibody, and hypocomplementemia. To avoid cyclophosphamide-related gonadotoxicity in this young girl, Rituximab was given. She was treated with two doses of Rituximab and there was complete resolution of her neuropsychiatric SLE. Rituximab can be considered over cyclophosphamide in children to avoid gonadotoxicity.